Kualitas Sistem Informasi Berdasarkan ISO/IEC 25010: Literature Review - Mulyawan, Made Dwi; Kumara, I Nyoman Satya; Swamardika, Ida Bagus Alit; Saputra, Komang Oka (Majalah Ilmiah Teknologi Elektro; Vol 20 No 1 (2021): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2021)
Abstract — Current information systems have become an important part of improving the effectiveness and efficiency of a business process, so we need a measurement of the quality of the software to determine the extent to which the system can produce quality information. In measuring quality, several models can be used as a guide in assessing software. ISO/IEC 25010 is one of the quality models that can be used as a standard in measuring software quality. ISO/IEC 25010 consists of the software product quality model and quality in use model. This article reviews some of the literature that discusses the measurement of software quality using the ISO/IEC 25010 model. Currently, the ISO/IEC 25010 has been applied to assess the quality of academic information systems, government information systems and private institutions, games, mobile applications, and decision support systems. The results of software quality assessment can be determined through the measurement of important aspects chosen based on the needs of each software. Besides the way the testing and data collection used in the assessment can affect the level of accuracy of software quality measurements.